Critical perspectives on the globally mobile professional and managerial class - McKenna, Stephen; Ravishankar, M.; Weir, D. (2015)
Purpose - The purpose of this paper is to introduce the papers in the special issue. Design/methodology/approach - A general description of each paper in the special issue is provided. The introduction highlights the need for more research into the broad topic of the global elite. Findings - Research in the social sciences uses a very broad definition of the global elite. It would be helpful in critical management and organization studies and critical international business research, to begin to identify important and key research areas that enable a more critical investigation of whom the global elite are and how they might be studied. Originality/value - This paper introduces five diverse papers that deal with issues pertaining to a global elite and transnational capitalist class.